Qur’anic quotation in the poetry of Abdul Mohsen Al-Kazemi - Rese. Muna Abd Abdulwahed; Dr. Jassim Hussein Al-Khalidi (Journal of College of Education, 2025)
The opinions of the ancients differed regarding the permissibility of quoting from the Holy Qur’an. Some of them did not allow it due to the sanctity of the Holy Qur’an, and some of them took a position defending the quotation and the permissibility of taking it, and some of them took a position defending the quotation and permissibility of taking from the Holy Qur’an, and that the words of the Creator should not be mixed with the words of the created being, and he has gone. Some scholars have come to say that quoting from the Holy Qur’an is based on legal acceptance and prohibition, because the Qur’anic text is a unique miracle in the arrangement of its verses, and it contains such significance, eloquence, and miracle that made writers and poets since the era of Islam and its dawn adopt its style and its presentation in their poetic forms, combining miracle and brevity. Therefore, we find that The religious text is the text that generates most of the patterns of behavior that penetrate Arab and Islamic cultural memory
Keywords: Qur’anic text , poets, quotation.